The Relation among Organizational Culture, Knowledge Management, and Innovation Capability: Its Implication for Open Innovation - Long Lam; Phuong Nguyen; Nga Le; Khoa Tran (Journal of Open Innovation: Technology, Market and Complexity, 2021)
It is widely acknowledged that enhancing innovation capability is an inevitable requirement for the survival and sustainable growth of firms operating in the information technology sector. Therefore, this study was conducted to explore the relationship among organizational culture, knowledge management and innovation capability in the open innovation environment to provide useful suggestions and recommendations for managerial practices within the high-tech industry. Primary data collected from 182 high-tech firm’s representatives were processed by using the Structural Equation Modeling approach. The results showed that knowledge management was strongly correlated with innovation capability. The positively significant relationship between organizational culture and knowledge management was also confirmed. Overall, the findings suggest that an open innovation culture of an organization in which mutual trust, collaboration and learning are promoted by supportive and participative leaders is more likely to increase the efficiency of knowledge management practices; thus, eventually lead to enhanced innovation capability of the firm.